Fostering scientific literacy and critical thinking in elementary science education - Vieira, Rui Marques (2017)
Scientific literacy (SL) and critical thinking (CT) are key components of science education aiming to prepare students to think and to function as responsible citizens in a world increasingly affected by science and technology (S&T). Therefore, students should be given opportunities in their science classes to be engaged in learning experiences that promote SL and CT, which may trigger the need to build and develop knowledge, attitudes/values, thinking abilities, and standards/criteria in an integrated way, resulting in their ability to know how to take responsible action in contexts and situations of personal and social relevance. This paper reports on a study to design, implement, and assess science learning experiences focused on CT toward SL goal. Results support the conclusion that the learning experiences developed and implement- ed in a grade 6 science classroom had a significant influence on the students’ CT and SL. Within this elementary school context, the theoretical framework used appears to be a relevant and practical aid for developing learning experiences that promote CT/SL and in supporting teaching practices that are more in line with the goals of critical scientific literacy.